In Silico Analysis of Bioactive Compounds in The Faloak (Sterculia quadrifida R. Br) Stem Bark to Identify Antidiabetic Activity - Utami, Fajar Dwi; Achmad Daud, Rizqi Akbar Fandi; Nurmayati, Adi; Ratumakin, Monika Buka Kopon; Siung, Chris Nicholas; Stephanie, Adiva; Fadillah, Almufti; Mulatsari, Esti; Mumpuni, Esti; Prasetyo, Andri (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Sterculia quadrifida R. Br or known as the faloak plant is a typical plant originating from the East Nusa Tenggara region, Indonesia. This plant has long been used by local people in the treatment of diabetes. In vivo, bioactive compounds from the extract of stem bark Sterculia quadrifida R. Br have been reported to have antidiabetic activity. The present study aims to analyse the potential of bioactive compounds in the faloak stem bark as inhibitors of the enzymes ?-glucosidase, PPAR-?, SGLT2, and DPP-IV. The preparation of bioactive compounds and their comparison was conducted utilising ChemDraw 2D & 3D, while proteins were obtained from the Protein Data Bank (PDB). The docking process used Molegro Virtual Docker, and visualisation was performed using BIOVIA Discovery Studio. Pharmacokinetic prediction (ADMET) was also carried out using the pkCSM website. The results of molecular docking with DPP-IV receptors showed that three bioactive compounds of faloak have better affinity than the comparative compounds, namely beta sisterol (-98.8838) to Alogliptin, Linagliptin, and Sitagliptin. While epicatechin (-83.9022) and cathecin (-83.4336) have better affinity than the comparative compounds Vidagliptin, Saxagliptin.